Pengaruh Fasilitas Kerja dan kepuasan Kerja Terhadap Kinerja Karyawan Lembaga Psikologi Widya Wiwaha Bekasi - Rasyad, Rifqi; Puspasari, Aprilia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the influence of work facilities and job satisfaction on employee performance at the Widya Wiwaha Psychology Institute in Bekasi. The background of this research is based on the importance of employees as the main asset of the organization, as well as the significant influence of work facilities and job satisfaction on motivation and performance. The method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through the distribution of questionnaires to 35 respondents who are employees of the institution, and analyzed using Statistical Product and Service Solution SPSS version 25. The research results show that work facilities (X1) do not have a significant effect on employee performance (Y) and job satisfaction (X2) has a significant effect on employee performance (Y), such as a comfortable work environment and adequate work tools, which can enhance employee work effectiveness. Similarly, high job satisfaction, demonstrated by good relationships with supervisors and colleagues as well as a conducive work environment, also contributes to increased productivity. Therefore, management needs to pay attention to these two variables as a strategy for sustainable HR performance improvement. This research is expected to serve as a basis for decision-making in improving organizational management, particularly in the psychological services sector.